2011
DOI: 10.1021/bi2002554
|View full text |Cite
|
Sign up to set email alerts
|

Strand Invasion of Mixed-Sequence, Double-Helical B-DNA by γ-Peptide Nucleic Acids Containing G-Clamp Nucleobases under Physiological Conditions

Abstract: Peptide nucleic acids (PNAs) are the only class of nucleic acid mimics developed to date that has been shown to be capable of invading double helical B-form DNA. Recently, we showed that sequence limitation associated with PNA recognition can be relaxed by utilizing conformationally-preorganized γ-peptide nucleic acids (γPNAs). However, like all the previous studies, with the exception of triplex-binding, DNA strand invasion was performed in relatively low salt concentrations. When subjected to physiological i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 37 publications
0
43
0
Order By: Relevance
“…18, 19 Ly and coworkers reported that incorporation of guanidino G-clamp residues into γPNA significantly enhances strand invasion into duplex DNA. 20 As shown in Scheme 1, hybridization of the 12mer or 6mer γPNA miniprobes to a complementary DNA of a given length will result in 1.5 or 3 times as many dyes being delivered to the target nucleic acid as the conventional PNA probe.…”
Section: Resultsmentioning
confidence: 99%
“…18, 19 Ly and coworkers reported that incorporation of guanidino G-clamp residues into γPNA significantly enhances strand invasion into duplex DNA. 20 As shown in Scheme 1, hybridization of the 12mer or 6mer γPNA miniprobes to a complementary DNA of a given length will result in 1.5 or 3 times as many dyes being delivered to the target nucleic acid as the conventional PNA probe.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, we did not observe any evidence of ligand binding taking place at a physiologically relevant ionic strength (Figure S21), indicating that the RNA hairpin was not able to mediate template-directed ligand oligomerization under such a condition. This outcome is unlikely due to the inability of ligand to access the H-bond donors and acceptors of RNA nucleobases, as we have demonstrated in the invasion of the DNA double helix by MP γ PNA, 80 but rather due to the lack of binding free energy. There are several ways in which the binding affinity of ligand can be improved.…”
Section: Resultsmentioning
confidence: 86%
“…Rapireddy et al have demonstrated that incorporation of an appropriate chiral substituent at the position in the PNA backbone induces right-handed helical pre-organization in the γPNA oligomers, enabling them to bind to double-stranded DNA targets via strand invasion with substantially increased affinity relative to standard PNAs [38]. In keeping with this, UV-melting analyses revealed that for both the MP γPNA1/DNA and MP γPNA2/DNA duplexes, the thermal stabilities were much higher than that of the PNA3/DNA (Supplemental Data, Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The gamma substitution creates chirality and provides helical pre-organization to the PNA oligomer, yielding substantially increased binding affinity to the target DNA [38]. The lack of editing by the mismatched γPNA, as well as the deep-sequencing results showing almost no effect at a partially homologous site, further demonstrates the specificity of binding by γPNAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation